“Prototipo de juego serio aplicando gamificación para la enseñanza – aprendizaje del idioma inglés en niños de tercer año de Educación Básica como parte del proyecto STEAM” - Ante Sinchico, Italo Stalin (2024)
The technological proposal was implemented at the Educative Unit "CERIT," located at the intersection of Sánchez de Orellana and Luis Ruiz streets in the Ignacio Flores parish, Latacunga Canton Cotopaxi province. The main objective was to develop a severe desktop game prototype, accompanied by a complementary web application for configuration. Low interest in learning English was identified among third-grade elementary school children, attributed to conventional teaching methods. In response, a severe game was proposed to integrate gamification strategies and STEAM approaches to enhance English language instruction. During the game development, detailed documentation was established regarding the methodologies, tools, and techniques. Additionally, interviews were conducted, and expert opinions in the relevant field were consulted to identify the user needs that needed to be addressed. Unity and C# were employed for game development, while PHP with Codeigniter was chosen for the web application. The Extreme Programming (XP) methodology was implemented to facilitate team collaboration and enable agile responses to programming changes. Kanban was used to optimize workflow and organize sprints and user stories. The combination of the game and the web application proved effective for game interactivity and allowed changes to be made from the web application. In conclusion, the serious game prototype significantly improved student interest and participation during learning activities at the "CERIT" Educational Institution.